2017
DOI: 10.1364/boe.8.003842
|View full text |Cite
|
Sign up to set email alerts
|

Increased prefrontal cortex connectivity during cognitive challenge assessed by fNIRS imaging

Abstract: In this study, functional near-infrared spectroscopy (fNIRS) and the graph theory approach were used to access the functional connectivity (FC) of the prefrontal cortex (PFC) in a resting state and during increased mental workload. For this very purpose, a pattern recognition-based test was developed, which elicited a strong response throughout the PFC during the test condition. FC parameters obtained during stimulation were found increased compared to those in a resting state after correlation based signal im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 76 publications
4
77
0
Order By: Relevance
“…The PFC serves a control function during routine cognitive operations, such as: action selection, retrieval/updating in working memory, monitoring and inhibition (Ramnani and Owen, 2004;Ridderinkhof et al, 2004). It is often activated during high levels of cognitive demand (Ayaz et al, 2012;Herff et al, 2014;Racz et al, 2017;Gateau et al, 2018;Fairclough et al, 2019) and dysfunction of this structure is known to degrade performance (Sandson and Albert, 1984;Dolcos and McCarthy, 2006). However, the PFC is complex and its function is subject to the quadratic influence of neuromodulation via the influence of noradrenaline and dopamine (Arnsten, 2009;Arnsten et al, 2012).…”
Section: The Non-linear Effects Of Neuromodulationmentioning
confidence: 99%
“…The PFC serves a control function during routine cognitive operations, such as: action selection, retrieval/updating in working memory, monitoring and inhibition (Ramnani and Owen, 2004;Ridderinkhof et al, 2004). It is often activated during high levels of cognitive demand (Ayaz et al, 2012;Herff et al, 2014;Racz et al, 2017;Gateau et al, 2018;Fairclough et al, 2019) and dysfunction of this structure is known to degrade performance (Sandson and Albert, 1984;Dolcos and McCarthy, 2006). However, the PFC is complex and its function is subject to the quadratic influence of neuromodulation via the influence of noradrenaline and dopamine (Arnsten, 2009;Arnsten et al, 2012).…”
Section: The Non-linear Effects Of Neuromodulationmentioning
confidence: 99%
“…Typically, DFC studies are conducted using fMRI, which is not appropriate for protocols requiring supine positions and/or non-elicited task execution. Recent studies have demonstrated that fNIRS is well positioned in such scenarios [47][48][49] . We foresee that implementing such approaches in the context of bimanual skill assessment can lead to refined skill level assessment metrics as well as potentially provide predictive models of skill acquisition.…”
Section: Submission Date: February 6thmentioning
confidence: 99%
“…39 Cui et al 32 also reported that the CBSI transformation reduced spikes in the data, modulated nonspike noise to improve signal quality (see Ref. 40 for supporting evidence), and improved spatial specificity of the signals. According to one recent paper, 41 there are five causes of positive association between HbO and HHb in the fNIRS signal, these are: (i) motion and head movement, (ii) cross-talk between the chromophores, (iii) differences in spatial responses due to the density of capillaries compared with large blood vessels, (iv) systemic effects from extracerebral sources, and (v) effects related to oxygenation and hemodynamic effects associated with muscle activation.…”
Section: Discussionmentioning
confidence: 97%